Aging analysis of textured water-repellent coatings under ultraviolet radiation and water - Myronyuk, Oleksiy; Baklan, Denys (Technology audit and production reserves, 2022)
The object of research in this work is a coating based on styrene butyl methacrylate binder and calcium carbonate modified with stearic acid. The existing problem is that the stability of the properties of superhydrophobic coatings when interacting with environmental factors – ultraviolet radiation, water vapor or dynamic action of water is limited. Establishing the relationship between the change in the chemical composition and texture of structured water-repellent surfaces under the influence of environmental factors is an essential step towards creating a stability model for such coatings. The work carried out is aimed at establishing the nature of the loss of water repellency of textured organo-mineral coatings under exposure to ultraviolet radiation in the UV-A range and water. UV resistance testing was performed in accordance with ASTM D 4329. The surface texture was examined using electron microscopy. The study of the change in chemical composition was performed using the IR spectroscopy method. As a result, it was shown that, under UV radiation, the most vulnerable component of organo-mineral coatings consisting of styrene-butyl methacrylate polymer and calcium carbonate modified with stearic acid is the polymer matrix, the oxidation of which leads to surface hydrophilization. The action of water in both static and dynamic modes leads to the loss of the upper layer of microparticles which forms the structure. It was found that in the surface layer of the polymer, upon irradiation with ultraviolet, the formation of polar carboxyl groups occurs at the initial stages of irradiation, which is accompanied by noticeable hydrophilization. Based on the obtained results, one of the ways to increase the resistance of additive water-repellent coatings to environmental factors can be the use of polymers that are more resistant to UV radiation. An alternative way is to use the optimization of the interfacial contact, which will ensure the slowing down of the loss of texture elements in the water environment.